Students’ Difficulties in Solving Higher Order Thinking Skills Problems on Algebra Content - Fathiya Salsabila; Rahmah Johar; Bahrun Bahrun (Proceedings of AICS - Social Sciences, 2018)
Higher order thinking skills are one of the thinking skills needed in the 21st century. HOTS can make students more critical, creative and innovative in solving problems. Students with HOTS can distinguish clear ideas, clear opinions, solve problems, formulate explanations well and understand complicated things become clear. However, the actual ability of HOT students is still low seen from their difficulties in solving HOTS problems. Therefore, this study aimed to describe students' difficulties in solving HOTS problems in algebra. This type of research was qualitative with descriptive method. The subjects of this study consisted of three students in the eighth grade at one of the junior high school in Banda Aceh. The instruments used were tests and interviews. The results showed that difficulties in understanding the information and questions given, the difficulty of finding patterns and relationships, difficulty in manipulating algebraic forms, lack of prerequisite materials, difficulty in solving equations that had been made, difficulties in understanding images in the form of information, difficulties in presenting images in the form of symbols or equations and difficulties in distinguishing the two-variable linear equation material and the two-variable linear equation system. By knowing the difficulties of students, it is expected that teachers and schools can provide learning that can reduce difficulties and develop HOTS abilities to enter the 21st century.Keywords: difficulty, higher order thinking skills, algebra.